PENGARUH MODAL KERJA, CASH FLOW DAN TOTAL ASET TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN BANK KONVENSIONAL YANG TERDAFTAR DI BEI PERIODE 2020-2022 - Ivanny, Levia Diza Dwi; Hamdun, Edy Kusnadi; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2024)
Banking companies are financial institutions whose job is to collect funds from the public in the form of deposits and then channel them back to the public in the form of credit or other things to advance the community's economy. Conventional banks themselves are banks that carry out their activities according to national and international regulations. This study aimed to determine the effect of working capital, cash flow and total assets on firm value with profitability as an intervening variable. This study uses quantitative and descriptive research. The population used in this study were 41 conventional bank companies listed on the IDX for the 2020-2022 period. The sampling technique used in this study was purposive sampling. Data analysis and hypothesis testing in this study using Smart PLS 3.0. The results of the direct effect test using the Smart PLS 3.0 application show that working capital has a positive but insignificant effect on profitability, cash flow has a negative but insignificant effect, total assets have a negative but insignificant effect, working capital has a positive but insignificant effect on firm value, cash flow has a negative but insignificant effect on firm value, total assets have a positive but insignificant effect on firm value, profitability has a negative but significant effect on firm value. The indirect effect hypothesis test results show that the working capital variable has a negative but insignificant effect on firm value through profitability, cash flow has a positive but insignificant effect on firm value through profitability, and total assets have a positive but insignificant effect on firm value through profitability.